The Modified-Delphi Technique: A Powerful Method for Health Waqf (Islamic Endowment) Modeling - Sulistyowati, Sulistyowati (Journal of Accounting and Finance Management, 2024)
The study aims to Identify the characteristics of the health waqf model; Designing various best models of health waqf; and finding the best model for health waqf in Indonesia. This research using the modified Delphi method. Result shows that there are 32 crucial aspects of healthcare waqf, of which respondents agree on 23 (71.88%) in a way that significantly increases rater agreement (W) or Kendall's concordance. Clinics, general hospitals, mother and child hospitals (RSIA), and specialty hospitals are some examples of the types of healthcare waqf that could be established at different levels based on the needs. The author suggests many healthcare waqf models, such as the 1) Social Healthcare Waqf Model (SHWM), 2) Productive Healthcare Waqf Model (PHWM), and 3) Integrated Social-Productive Healthcare Waqf Model (ISPHWM), based on the established characteristics. The outcomes of the suggested healthcare waqf models are most suited for implementation in Indonesia because the study's respondents are Indonesian professionals and practitioners. Nonetheless, the approach taken and the model framework that came from this research could be utilized to identify the features of healthcare waqf and suggest the best models in other nations.